Spread of combined liver and kidney pathology in dogs in the city of Poltava - Rudyashko, V. (Scientific Progress & Innovations, 2025)
A significant part of non-contagious internal pathologies in small-size animals, particularly domestic dogs, consists of the digestive and urinary systems’ diseases. Liver and kidney diseases and their clinical and pathogenetic interrelationship are always a relevant subject of scientific research. The study results on the spread of combined liver and kidney pathology in domestic dogs in the city of Poltava during the period of 2021-2024 are presented in the article, taking into account the nosological structure, chronology of diagnosing, the age of diseased animals, and seasonality of the diseases’ manifestation. The aim of the study was to investigate the simultaneous occurrence of liver and kidney pathology in dogs, taking into account the chronology, age, and seasonality of manifestation.The object of the study was the data from the registers of diseased animals and the results of laboratory and ultrasonographic examinations of veterinary clinics in Poltava during 2021-2024. The results of examinations of 1,256 dogs aged from one to 12 years with clinical and laboratory symptoms of hepatic-biliary and/or urinary system lesion were analyzed. It was found that the share of combined liver and kidney pathology in dogs averaged 24.0 %. The relative number of dogs in which liver pathology is accompanied by kidney lesion was determined: at acute hepatitis – 42.5 % of cases, at chronic hepatitis – 33.6 %, at hypertrophic cirrhosis of the liver – 12.3 %, at hepatolipidosis – 8.0 %, at atrophic cirrhosis of the liver – 3.7 %. It was found that during 2021-2024, the frequency of diagnosing combined liver and kidney pathology in dogs in the city of Poltava increased by 31.1 %. The predominant age of combined liver and kidney pathology manifestation in dogs is 6-8 years. The share of chronic diseases grows proportionally with the age of dogs up to 8 years and decreases at the age of 9-12 years. In dogs aged 1-2 years, kidney lesion is more often accompanied by acute inflammatory liver diseases than by chronic diseases. The seasonality of combined liver and kidney pathology occurrence in dogs is characterized by the increase in morbidity in spring and autumn (acute and chronic hepatitis complicated by nephropathy), and complications of hepatolipidosis – in the winter-spring period.